Pengembangan Modul Pembelajaran Digital Berbasis Model Sq3r pada Materi Teks Narasi terhadap Kemampuan Membaca Pemahaman Siswa Kelas V SDN Tanjung Jati 2 - Najwa Salma Khoirun Nisa; Conny Dian Sumadi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Learning materials used in elementary schools are still primarily limited to printed textbooks and have not been systematically designed to support the stages of reading comprehension. As a result, many fifth-grade students continue to experience difficulties in understanding texts, identifying explicit information, and drawing conclusions from reading passages.This research and development aims to determine the validity, practicality, and effectiveness of the digital learning module based on the SQ3R model on narrative text material towards the reading comprehension ability of fifth-grade students of SDN Tanjung Jati 2. This study uses the Plomp development model which consists of three stages, namely preliminary research, development phase, and assessment phase. The research subjects include material experts, learning design experts, and teaching material experts as validators. Individual tests were conducted on 3 sixth-grade students, small group tests on 6 sixth-grade students, and field tests on 19 fifth-grade students. The results of the study showed that the developed module met the criteria of validity, practicality, and effectiveness. The validity of the product was shown by the validation results of material experts at 82%, learning design experts at 97%, and teaching material experts at 96%. The practicality of the product was shown through observations of teacher activities at 96.65% and student activities at 92.05%. The effectiveness of the product was shown by classical learning completeness at 94.73%. Thus, the digital learning module based on the SQ3R model is declared valid, practical, and effective for use in learning Indonesian in elementary schools.